The influence of target layout and target graphic type on searching performance based on eye-tracking technology - Zuo, Yaxue; Qi, Jin; Fan, Zhijun; Wang, Zhenya; Xu, Huiyun; Wang, Shurui; Zhang, Nieqiang; Hu, Jie (Frontiers in Psychology, 2023)
With the development of various intelligent technologies, the application of interactive interfaces is becoming more and more widespread, and the related researches conducted for interactive interfaces are also increasing. The purpose of this study was to explore the influence of icon layout location, icon graphic type, and icon layout method on users’ searching performance in interactive interfaces through eye-tracking technology. Participants were asked to perform search tasks for the search target (facet icon or linear icon) on each image. Thus, each trial consisted of a search task on a given image. In total, each participant had 36 trials to complete. Searching time, fixation duration, and fixation count were collected to evaluate the searching performance of participants. Results showed that when faced with familiar icons, whether the graphic type of icons was facet or linear did not affect the user’s experience, but when other factors of the interaction interface changed, facet icons provided a more stable experience for users. And compared to the rectangular layout, the circular layout method provided a more stable experience for users when the location of icons in the interactive interface changed, but icons located in the top half of the interactive interface were easier to find than those located in the bottom half, regardless of whether the layout was circular or rectangular. These results could be used in the layout and icon design of the interactive interfaces to facilitate their optimization.